Green electricity certificates: A supplement to the flexible mechanisms of the Kyoto protocol - Lene Nielsen; Tim Jeppesen (Fondazione Eni Enrico Mattei (FEEM), 1999)
With the liberalisation of the European electricity market, new instruments are searched for in order to co-ordinate climate change initiatives with competition. This paper analyses the potential of a system of green electricity certificates to regulate the introduction of renewable energy sources. Based on Dutch experiences from a similar system of Green Labels, potential problems and possible solutions are presented. Furthermore, the system of Green Certificates is compared with the flexible mechanisms of the Kyoto Protocol in order to discuss their common features and assess the compatibility of these instruments.
Keywords: L51; Q42; Q48; 330; Renewable energy; Regulation; Green Certificates; Liberalisation; Subsidiarity; the Kyoto Protocol; Erneuerbare Energie; Umweltzeichen; Umweltpolitik; Emissionshandel; Theorie; Dänemark